Giảng dạy tiếng Anh như ngôn ngữ thứ hai trong trường học: Kinh nghiệm tại Singapore, Philippines, Nam Phi và hàm ý chính sách cho Việt Nam - Nguyễn, Hảo; Vũ, Nga (Tạp chí Giáo dục, 2026)
Resolution No. 71-NQ/TW, dated August 22, 2025, of the Politburo on Breakthroughs in Education and Training has set forth requirements to strengthen foreign language education and gradually establish English as a second language in schools, thereby revolutionizing the teaching and learning of English. English has evolved from a required subject into a tool for teaching other subjects. This shift has been taking place in many countries around the world since the 1990s in various forms. During the initial phase of this transition, difficulties and challenges arose due to both subjective and objective factors, with teachers’ ability to teach in English playing a central role. Using a review, analysis, and comparison approach, this article examines the experiences of Singapore, the Philippines, and South Africa in using English as a second language in schools from a policy perspective. Consequently, the paper offers several lessons for Vietnam in the process of policy formulation and enhancing the effectiveness of English teaching and learning, thereby contributing to advancing the process of making English a second language in teaching and learning at educational institutions in the new context. The research findings provide a scientific foundation for studies on the teaching of English as a second language in schools, as well as a practical basis for policy-making and the implementation of the making English the second language in schools during 2025-2035, with a vision to 2045” project.